2018
DOI: 10.1038/eye.2018.1
|View full text |Cite
|
Sign up to set email alerts
|

Cat-PROM5: a brief psychometrically robust self-report questionnaire instrument for cataract surgery

Abstract: PurposeTo develop a short, psychometrically robust and responsive cataract patient reported outcome measure suitable for use in high-volume surgical environments.MethodsA prospective study in which participants completed development versions of questionnaires exploring the quality of their eyesight using items harvested from two existing United Kingdom developed parent questionnaires. Participants were 822 patients awaiting cataract surgery recruited from 4 cataract surgical centres based in the UK. Exclusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 20 publications
0
37
0
Order By: Relevance
“…Participants' refractive errors were collected using an RK-501A Autorefractor (Nidek Co. Ltd, Aichi, Japan). a Rasch calibrated psychometrically robust measure which is highly responsive to cataract surgery, in which a higher score indicates greater visual disability 17,18 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants' refractive errors were collected using an RK-501A Autorefractor (Nidek Co. Ltd, Aichi, Japan). a Rasch calibrated psychometrically robust measure which is highly responsive to cataract surgery, in which a higher score indicates greater visual disability 17,18 .…”
Section: Methodsmentioning
confidence: 99%
“…Our aim was to complete the largest RCT published to date comparing FLACS with CPS with the intention to inform clinical practice and health policy worldwide. As there have been a lack of patient reported outcome measures (PROMs) in previous RCTs, this study aimed to correct this by measuring quality of life with EuroQOL's EQ-5D and patient reported quality of vision with Cat-PROM5 17,18 .…”
Section: Introductionmentioning
confidence: 99%
“…All participants completed the Cat-PROM5 and ICECAP-O. The Cat-PROM5 is a fiveitem questionnaire designed to measure the HRQL impact of cataract surgery [22]. The Cat-PROM5 is responsive to changes in vision following cataract surgery (Cohen's d = -1.45) [22], although is not preference based and thus cannot be used in CUA.…”
Section: Data Collectionmentioning
confidence: 99%
“…The Cat-PROM5 is a fiveitem questionnaire designed to measure the HRQL impact of cataract surgery [22]. The Cat-PROM5 is responsive to changes in vision following cataract surgery (Cohen's d = -1.45) [22], although is not preference based and thus cannot be used in CUA. It is currently being piloted in the National Ophthalmology Database Cataract Surgery Audit [23], its use having been encouraged by NICE [24].…”
Section: Data Collectionmentioning
confidence: 99%
“…Secondary outcome measures were TIOL rotational stability data and safety data for both groups. Following an amendment to the protocol during the study, patient-reported outcome measures (PROMs) were studied using Cat-PROM5 [ 7 , 8 ] questionnaire as well as EuroQOL EQ-5D quality of life questionnaire with visual analogue score (VAS) ( https://euroqol.org ).…”
Section: Surgical Techniquementioning
confidence: 99%